Inhibiting cycloxygenase and ornithine decarboxylase by diclofenac and alpha-difluoromethylornithine blocks cutaneous SCCs by targeting Akt-ERK axis. - Aadithya Arumugam; Zhiping Weng; Sarang S Talwelkar; Sandeep C Chaudhary; Levy Kopelovich; Craig A Elmets; Farrukh Afaq; Mohammad Athar (PLoS ONE)
Non-melanoma skin cancer (NMSC) is the most common type of skin cancer in Caucasian populations. Its increasing incidence has been a major public health concern. Elevated expressions of ODC and COX-2 are associated with both murine and human NMSCs. Inhibition of these molecular targets singly employing their respective small molecule inhibitors showed limited success. Here, we show that combined blockade of ODC and COX-2 using their potent inhibitors, DFMO and diclofenac respectively abrogates growth of A431 epidermal xenograft tumors in nu/nu mice by more than 90%. The tumor growth inhibition was associated with a diminution in the proliferation and enhancement in apoptosis. The proliferation markers such as PCNA and cyclin D1 were reduced. TUNEL-positive apoptotic cells and cleaved caspase-3 were increased in the residual tumors. These agents also manifested direct target-unrelated effects. Reduced expression of phosphorylated MAPKAP-2, ERK, and Akt (ser(473) & thr(308)) were noticed. The mechanism by which combined inhibition of ODC/COX attenuated tumor growth and invasion involved reduction in EMT. Akt activation by ODC+COX-2 over-expression was the key player in this regard as Akt inhibition manifested effects similar to those observed by the combined inhibition of ODC+COX-2 whereas forced over-expression of Akt resisted against DFMO+diclofenac treatment. These data suggest that ODC+COX-2 over-expression together leads to pathogenesis of aggressive and invasive cutaneous carcinomas by activating Akt signaling pathway, which through augmenting EMT contributes to tumor invasion.